2018
DOI: 10.18311/ijmds/2013/19825
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Precancerous Lesions of Oral Cavity

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The main aim of the current study was to obtain epidemiological profile of OPMD and OSCC in the last 7 years in two districts of Karnataka to obtain a better estimate of total cases. [ 15 16 ] Based on our data, the prevalence of OPMD and OSCC in both districts might be linked to a rise in the usage of tobacco in various forms, areca nut and alcohol, compared to other districts. In addition, most of the OPMD cases were in the fourth decade similar to Misra et al [ 7 ] However, Scott and Cheah and Waldern and Shafer found most of their cases in sixth and seventh decades, respectively, which might be due to the cumulative effect of tobacco carcinogens.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The main aim of the current study was to obtain epidemiological profile of OPMD and OSCC in the last 7 years in two districts of Karnataka to obtain a better estimate of total cases. [ 15 16 ] Based on our data, the prevalence of OPMD and OSCC in both districts might be linked to a rise in the usage of tobacco in various forms, areca nut and alcohol, compared to other districts. In addition, most of the OPMD cases were in the fourth decade similar to Misra et al [ 7 ] However, Scott and Cheah and Waldern and Shafer found most of their cases in sixth and seventh decades, respectively, which might be due to the cumulative effect of tobacco carcinogens.…”
Section: Discussionmentioning
confidence: 81%
“…To achieve this goal, dentists play a pivotal role in educating the public, diagnosis and long-term follow-up of patients at risk and to avoid local recurrence and lymph node metastases. [ 8 9 14 15 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study done by Pooja et al in 1999 to assess the role of serum iron, ferritin as well as total iron binding capacity (TIBC) in the pathogenesis and treatment planning of OSMF and Leukoplakia, showed that about 88% of patients with oral leukoplakia and OSMF (22) were males and 12% (03) were females. 10 The mean folate level with SD (ng/dl) was found to be 5. 12 Similarly, another study done by Guruprasad R et al to assess the serum vitamin C and iron levels in oral submucous fibrosis with 35 patients showed that iron levels was significantly decreased in OSMF patients than in controls.…”
Section: Discussionmentioning
confidence: 94%
“…Collective estimate of annual rate of OL malignant transformation is 1.36% (95% confidence interval, 0.69–2.03%) in various populations and geographical areas. [ 1 ] The World Health Organization group has defined leukoplakia as “a white patch or plaque that cannot be characterized, clinically, or pathologically, as any other disease.”[ 2 ] Scarcely a few decades ago, a rare form of OL known as PVL was described, first by Hansen et al . in 1985.…”
Section: Discussionmentioning
confidence: 99%
“…A PMOL has been defined as a lesion or condition, in which risk of malignancy, being present at the time of initial diagnosis or at a future date. [ 2 3 ] Leukoplakia is the most common potentially malignant lesion of the oral mucosa and among all proliferative verrucous leukoplakia (PVL), distinct clinical form of oral leukoplakia (OL), is a rare potentially malignant oral mucosal disorder with a high rate of progression to oral SCC (OSCC) and verrucous carcinoma (VC). [ 4 ] The condition develops initially as focal clinical hyperkeratosis that progressively becomes a wide multifocal disease with gross exophytic features.…”
Section: Introductionmentioning
confidence: 99%